2013
DOI: 10.4172/2153-0602.1000142
|View full text |Cite
|
Sign up to set email alerts
|

The Family Knowledge about the Disease and Complications Risk among Diabetic Patients-in Poland

Abstract: Taking care of diabetic patients involves a family which is perceived as an environment, whose support is a factor that best forecasts implementation of required recommendations for diabetes care. The ability of family to support patients' effort can improve diabetes care results. The aim of this work is to indicate how family knowledge about the disease diversifies a medical condition and complications risk among diabetic patients. Research has been carried out within the scope of NCSR grant no. 6P05D02320, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The respondents' levels of knowledge varied significantly due to their personal experience of being a diabetic or having a diabetic person in the family. These results correspond with the results of other studies aimed at assessing the awareness of diabetes-related issues among different patient groups [32,33] and in the general population [34,17] in Poland.…”
Section: Discussionsupporting
confidence: 90%
“…The respondents' levels of knowledge varied significantly due to their personal experience of being a diabetic or having a diabetic person in the family. These results correspond with the results of other studies aimed at assessing the awareness of diabetes-related issues among different patient groups [32,33] and in the general population [34,17] in Poland.…”
Section: Discussionsupporting
confidence: 90%
“…Some other studies carried out in South Africa [13], Ethiopia [14] and Kenya [15] indicated that diabetic patients and their family members lack sufficient knowledge on diabetes and its management. Furthermore, in a study carried out in Poland [16], more than half (56%) of family member caregivers' had no knowledge about diabetes risk factors and complications. In another study carried out in Ethiopia [17], it was observed that 78.3% of primary and secondary diabetic patient's family members had good level of knowledge about diabetes and its prevention and this was almost 3-folded that of control group.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledgeable family members/caregivers of diabetic patients usually express more care for their patients and consequently better control and less complications. In a study carried out in Poland, Abramczyk observed that diabetic patients of more knowledgeable family members/caregivers showed more care regarding oral hygiene, self-care, selfmanagement, in addition, they had no somatic or psychoemotional complaints, no additional medical problems and their weight, blood pressure, and triglycerides were normal [16], However, in a systematic review carried out by Baig et al, they cannot determine how family members participation in diabetes management can affect patient's clinical outcomes [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Last-but-not least, the final 2 papers in this issue of the Journal have direct relevance to patient care in families and clinics. In her paper 'The Family Knowledge about the Disease and Complications Risk among Diabetic Patients-in Poland' , A. Abramczyk summarizes results from the analysis of 1366 questionnaires from families/ caregivers of diabetic patients randomly chosen from 61 primary healthcare centers in Poland [9]. The high significant results demonstrate that family knowledge about the disease is a significant factor that diversifies a medical condition of diabetic patients and a higher level of knowledge among family members about the disease improves patients' medical condition and reduces the risk of diabetes complications.…”
mentioning
confidence: 99%